Determination of Transport and Thermal Properties of Silicon Samples by the Phase-Lag and Sf/Sr Methods - CHROBAK, Łukasz; MALIŃSKI, Mirosław (Archives of Acoustics, 2009)
The paper presents results of photoacoustic studies of thermal and transport properties of silicon samples. It shows for the first time the influence of plasma waves on the Sf/Sr and phase-lag frequency photoacoustic characteristics and describes a procedure leading to the determination of both thermal diffusivity and the life time or the diffusion length of excess carriers from those characteristics.